Perencanaan dan Perancangan Kampus UNSIKA dengan Penekanan pada Konsep Arsitektur Vernakular - Aguswin, Ahmad; Manalu, Tigor David; Fathurochman, Achmad (Universitas Pelita Bangsa, 2021)
in the city of Karawang. The goal and objective of the planning and design of the UNSIKA II Campus is to provide unique building characteristics from the locality of Karawang, namely Kota Lumbung Padi. The methods used to achieve the final design are field survey, data collection, data analysis, concept and final design. The basic design concept includes a discussion of site data, along with the area of ​​the building to be constructed. Circulation within the site includes circulation for pedestrians, two-wheeled vehicles, four-wheeled vehicles, bicycles and the disabled. And it has three large masses which are the rectorate building, laboratory and library. In achieving this goal, the Karawang City Logo is used. These features are taken and applied to the building mass and site plan pattern to provide a modern and traditional atmosphere. Choosing the theme of Vernacular Architecture in accordance with the surrounding community is considered suitable for campus buildings, this is because local values ​​start to disappear along with the passage of time.